New-Onset Diabetes Mellitus With Exposure to Ledipasvir and Sofosbuvir - Resmi Premji MD; Nira Roopnarinesingh MD; Nazia Qazi MD; Eric S Nylen MD (SAGE Publishing, 2015)
The combination therapy of ledipasvir/sofosbuvir was approved by the Food and Drug Administration in 2014 for the treatment of chronic hepatitis C. Although hyperglycemia is not well known to occur with its use, we present 2 cases of new-onset diabetes mellitus and a review of the literature suggesting an adverse event association. In the first patient with HIV, we postulate that ledipasvir/sofosbuvir increased the levels of tenofovir and thereby potentiated hyperglycemia. In the second case of a patient with prediabetes, ledipasvir/sofosbuvir appeared to increase insulin resistance. A literature review further supported an association of hyperglycemia and the use of ledipasvir/sofosbuvir. Hence, clinicians should be cautious about worsening of glucose intolerance, and more studies are warranted to explore the underlying mechanism.